Correlations between peak power output, muscular strength and cycle time trial performance in triathletes - Bentley, D. J.; Wilson, G. J.; Davie, A. J.; Zhou, S. (The Journal of Sports Medicine and Physical Fitness, 1998)
OBJECTIVE: To examine the relationship between the peak power output (Wmax), peak oxygen uptake (VO2peak), lower limb muscular strength and cycling time (CT) during a short course triathlon race. EXPERIMENTAL DESIGN: The study involved a cross-sectional analysis involving both physiological and biomechanical variables. SETTING: Testing was performed at the exercise physiology and biomechanics laboratory, School of Exercise Science and Sport Management, Southern Cross University, Lismore, Australia. PARTICIPANTS: Ten male triathletes who had been endurance cycle training for a minimum of 12 months prior to the commencement of the study. MEASURES: Subjects completed a maximal incremental cycle test as well as a series of muscular function tests including a 6-s cycle test, a concentric isoinertial squat jump as well as an isokinetic leg extension test performed at velocities of 60 degrees (s-1, 120 degrees (s-1 and 180 degrees.s-1. In addition, each subject also participated in a triathlon race of distance 1.5 km swim, 40 km cycle and 10 km run. RESULTS: A significant correlation existed between CT and absolute VO2 peak and Wmax. However, no significant correlations were found between the results of the muscular function tests and the incremental cycle test as well, as CT during the triathlon race. CONCLUSIONS: Wmax and WDmax are useful variables in assessing cycle performance in triathletes. However, the importance of muscular strength of the lower limbs may be minimal in overall cycle performance during a short course triathlon race.